Invalid votes in the election practice of selected countries – causes and consequences - Gałązka, Marta (Politologia, 2023)
This text analyses the causes for invalid votes. On one hand this may be caused by the ignorance of the voters, but on the other hand it can also be the result of a conscious decision. There are also some causes attributed to the election organizers (law makers, election commissions) and the applied election techniques. The article provides a detailed analysis of the presidential election in the USA in 2000, in which the election result was questioned due to misleading ballots and the way they were treated by the machines used in the election counting process, and the elections in Romania, in which the losing party accused the winners of election fraud on several occasions.